Large Anthrax Outbreak in a New Locality in Croatia, 2022 - Žmak, Ljiljana; Bošnjak, Selma; Pem Novosel, Iva; Juzbašić, Tajana; Vilibić-Čavlek, Tatjana; Tabain, Irena; Miškić, Tihana; Lohman Janković, Ivana; Brkić, Inoslav; Gverić Grginić, Ana (Life (Basel, Switzerland), 2024)
Bacillus anthracis is a well-known zoonotic pathogen that can cause disease in both animals and humans. Moreover, it has a high bioterrorism potential as its lethal spores are resistant to inactivation, are easy to produce in large quantities, and are easily spread over large areas. Anthrax cases occur in different parts of the world, including most European countries. Specific areas of Croatia are long known as anthrax districts, but with sporadically reported cases over the years. Here, we present a major outbreak of animal and human anthrax in the region of Lonjsko Polje in Croatia, a region not known to have anthrax cases in the past. The outbreak started in July 2022 and lasted several months, but most human and animal cases were reported in the first month. During the outbreak, there were 17 reported human cases of cutaneous anthrax and 29 laboratory-confirmed animal cases. However, due to issues in reporting in animals and the late finding of the carcasses, which made laboratory diagnostics challenging, the actual number of animal cases was probably significantly higher.